UMPASA (PANTUN) DALAM UPACARA ADAT PERNIKAHAN MASYARAKAT BATAK TOBA DI KECAMATAN SILIMA PUNGGA-PUNGGA KABUPATEN DAIRI. - Siagian, Elister; Saiman, M.Pd, Drs. Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: umpasa is the type rhyme in kesusastraan the Batak Toba. Umpasausually used in every ceremony education customary. In the wedding ceremony thecommunity Batak Toba, umpasa always conveyed in stages marriage Batak Toba.Delivery of umpasa in traditional ceremonies marriage Batak Toba in general notdependent on the Raja Parhata , but family members especially the hula-hula. Deliveryof umpasa also based on the principles of “Dalihan Na Tolu”. The use of umpasa willbe never free of traditional ceremonies marriage Batak Toba because umpasa that wasdelivered at the wedding ceremony customary Batak Toba having a meaning that is asprayer , blessing or request to of the lord against family of his bride or wholly. Methodsused in research this is the method of historical research or historically. As for researchlocations that is in kecamatan Silima Pungga-pungga. Time research in starts test aproposal to with an examination thesis. Technique data collection used the techniqueobservation , the literature study , and interview.Key Words: Umpasa, Marriage was toba